Influence of plant growth regulators on severity of post harvest fruit rots of guava and citrus fruits (Indian Journal of Arid Horticulture, 2013)
Post-harvest disease management is one of the  biggest challenges in intensive fruit production systems.  Compare to the vast production of fruits in India, the fruit  export from the country has been negligible. A major  constraint has been the enormous losses to fruits have been  estimated to be in the range of 5-50% or more of the  harvest. The fruit-exporting countries have strict requirements to meet health standards. These requirements  have adversely affected the fungicide application on  harvested fruits. The search for alternative treatments have  yielded positive results with homeopathic drugs, hot water  treatment, plant growth regulators has proved effective  against post harvest diseases of harvested fruits. Applications of Gibberallic acid reduced diseases .
Keywords: fruit-exporting; Godara, 1994